ASSAY OF Acinetobacter AS COMPETITOR TO VIBRIOSIS LUMINESCENCE BACTERIA IN PACIFIC PACIFIC WHITE SHRIMP(Litopenaeus vannamei) - Assovaria .; Esti Harpeni; Asep Saefulloh (Jurusan Perikanan dan Kelautan, 2015)
Pacific white shrimpculture is having problems caused by bacteria infection. The cause of bacteria infection is V. harveyi, it can decrease seed production. Pathogenicity of vibriosis can decrease with inhibition by other types of bacteria. The aim of the research was to get competitor V.harveyi isolates through identification and challenge test in vitro and in vivo. The result of screening of bacterial isolates were obtained from cultivation supplement products to produced 4 pure isolates with different morphologically colonies and cells. There was one potential isolate could inhibits V. harveyi by inhibition test in vitro. Biochemical test from three different laboratories were identified that Acinetobacter sp. as competitor to V. harveyi and it was not pathogenic to Pacific white shrimp. Challenge test Acinetobactersp. against V. harveyi on Pacific white shrimp larvae was conducted through three treatments, without given V.harveyi and Acinetobacter sp. As controls; treatment with given bacteria V.harveyi and treatment with given V. harveyi and Acinetobacter sp. The challenge test results showed that treatment with given of V.harveyi and Acinetobacter sp. may decreased V. harveyi density of 6.3x106CFU/mL to 7.5x103CFU/mL which could suspected to decrease pathogenicity of competition number of colonies.